Symbolic Interactionism and Grounded Theory: a way for nursing to understand the meanings - Susana Ivette Natera-Gutiérrez; Raúl Fernando Guerrero-Castañeda; Ma. Elena Ledesma-Delgado; Ma. Guadalupe Ojeda-Vargas (Universidad de Alicante, 2018)
Objective: To analyze the concepts of meaning, symbolic interactionism and grounded theory, arguing the differentiation and proposing them for qualitative research in nursing. Methodology: A theoretical essay was performed based on the analysis of the concepts of Meaning, Symbolic Interaccionism and Grounded Theory based on bibliography related to the subject, interrelating them through reflection to build an argument that allows to differentiate the concepts and integrate them as a proposal for Qualitative Research in nursing. Results: Qualitative research departs from the data expressed by humans in various ways, generally they are constructions of the world around them and represented by symbols that are called meanings. These meanings are intimately related to life, health, disease and care, so it is imperative for nursing to understand the meanings that are given in humans, that understanding is given by the interpretation of the same in speeches. Conclusions: It is necessary to distinguish the symbolic interactionism as a theoretical or referential axis and the grounded theory as a methodological axis. The grounded theory gives methodological support in the process and leads the interpretation of human interactions in which the nurse is immersed.